201 COVID-19 Pandemic Sleep Disturbances Related to Stress Experiences at the US-Mexico Border. (3rd May 2021) - Begay, Tommy; Valencia, Dora; Ghani, Sadia; Delgadillo, Marcos; Madhivanan, Purnima; Krupp, Karl; Ruiz, John; Seixas, Azizi; Jean-Louis, Giardin; Killgore, William; Wills, Chloe; Grandner, Michael
Abstract: Introduction: The COVID-19 pandemic has impacted many individuals at the vulnerable US-Mexico border region in a variety of ways. Fear, worry, and stress have increased for many, as has poor sleep. The present study evaluated the degree to which worsened sleep due to the pandemic impacted stress experiences. Methods: Participants were N=155 individuals who completed the Nogales Cardiometabolic Health and Sleep (NOCHES) and were contacted about completing a COVID sub-study (95% Hispanic/Latino). They were asked the degree to which their sleep worsened due to the pandemic. They also reported the degree to which they agreed with statements regarding various pandemic-related stress experiences. These included infection-related stresses, stresses about community impact, personal psychosocial stresses, stresses about consequences of potential infection, media and society-related stresses, feelings of safety, and how the pandemic has impacted home life. Ordinal logistic regressions were used to determine whether changes in sleep were associated with agreement with statements about pandemic-related stress experiences, adjusted for age, sex, financial status, education, and mental health (PHQ4). Results: Those who perceived that their sleep worsened were more likely to report greater endorsement of beliefs that they were infected (ordinal Odds Ratio [oOR]=2.82, p<0.0005), they could possibly be infected (oOR=1.98, p=0.003), they feared testing (oOR=1.94, p=0.006), COVID-19 would impact their community (oOR=1.75, p=0.017) and would do so for a long time (oOR=1.90, p=0.006), they experience more general (oOR=4.10, p<0.0005), financial (oOR=3.15, p<0.0005), food-related (oOR=2.97, p<0.0005), housing-related (oOR=2.14, p=0.002), family-related (oOR=2.53, p<0.0005) and relationship (oOR=3.37, p<0.0005) stress, their shopping was impacted by scarcity (oOR=1.76, p=0.014), and they are at high risk for COVID (oOR=1.87, p=0.008). Furthermore, media coverage of COVID-19 had increased their stress (oOR=2.46, p<0.0005), there is too much panic about COVID-19 (oOR=1.67, p=0.032), and they themselves are scared of getting COVID-19 (oOR=1.95, p=0.005), worried about the future (oOR=1.71, p=0.022), feel less secure (oOR=0.59, p=0.028), are thriving less (oOR=0.40, p<0.0005), and their mental health is not improving (oOR=0.46, p=0.002). Conclusion: Worse sleep due to the COVID-19 pandemic was associated with increased reports of stresses across a wide range of domains. Perhaps sleep health interventions could improve social and emotional health in these domains and reduce stress experiences and better cope with the pandemic. Alternatively, mental health interventions should perhaps be targeted to this population. Support (if any): R01MD011600, R01DA051321